Toxicokinetics of the plasticizer, N-butylbenzenesulfonamide, in plasma and brain following oral exposure in rodents: Route, species, and sex comparison. (2020) - Waidyanatha, Suramya; Gibbs, Seth; South, Natalie; Smith, Jeremy P.; Mutlu, Esra; Burback, Brian; Cao, Yu; Rider, Cynthia V.
Highlights: The kinetics of N- butylbenzenesulfonamide (NBBS) was investigated in rodents. NBBS was rapidly absorbed following gavage exposure in rodents. It was rapidly eliminated with a half-life ≤3.5 h. Bioavailability following gavage administration was high. Systemic exposure was higher following gavage exposure than following via feed. Abstract: N-Butylbenzenesulfonamide (NBBS) is a widely used plasticizer and hence there is potential for human exposure via oral routes. This work investigates the toxicokinetic behavior of NBBS in rodents following a single gavage (20, 60, and 200 mg/kg body weight) or multi-day feed administration (500, 1000, and 2000 ppm). In male and female rats following gavage administration, maximum plasma NBBS concentration, Cmax, was reached at ≤0.539 h. Cmax increased proportionally to the dose. Area under the curve (AUC) increased more than proportionally to the dose and was 4- to 5-fold higher in females than in males. In mice, plasma Cmax was reached at ≤0.136 h and increased proportionally to the dose in female mice and more than proportionally to the dose in males. AUC increased more than proportionally to the dose with no apparent sex difference. Elimination of NBBS in plasma was faster in mice (half-life (h); mice ≤0.432, rat ≤3.55). Oral bioavailability was higher in female rats (≥60%) than males (23-52%) with apparent saturation of clearance at ∼200 mg/kg body weight in females. In mice, bioavailability (5-14%) was lower with no apparent sex difference. NBBS was detected in brains of rats and mice but with low brain:plasma ratios (rats, ≤5; mice, ≤1) suggesting low potential to cross the blood brain barrier. Systemic exposure in male rats and mice following a single gavage administration was ≥48-fold higher than multi-day feed exposure. These data demonstrate potential species, sex, dose- and route-related difference in toxicokinetics of NBBS in rodents.